Pengaruh Budaya Kerja dan Kepuasan Kerja terhadap Produktivitas Kerja Aparatur Sipil Negara pada Biro Sumber Daya Manusia Kementerian Kependudukan dan Pembangunan Keluarga Pusat Jakarta Timur - Nia Syahrani; Suryanto Sosrowidigdo; Siti Nurjanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the influence of work culture and job satisfaction on the work productivity of State Civil Apparatus (ASN) employees at the Human Resources Bureau of the Ministry of Population and Family Development, East Jakarta. Employee productivity is considered an important indicator of organizational effectiveness, particularly in public institutions responsible for delivering quality public services. The research employed a quantitative approach with a causal research design. A saturated sampling technique was applied, involving all 46 ASN employees as respondents. Primary data were collected through structured questionnaires using a five-point Likert scale and analyzed using SPSS version 25. The results indicate that work culture does not have a significant partial effect on employee work productivity (Sig. = 0.372 > 0.05; t = 0.901 < t-table = 1.681). In contrast, job satisfaction has a positive and significant influence on work productivity, making it the strongest determinant among the variables examined. Simultaneously, work culture and job satisfaction significantly affect employee productivity (F = 25.487 > 3.214; Sig. = 0.000). The coefficient of determination (R² = 0.542) shows that 54.2% of the variation in work productivity is explained by the proposed model, while the remaining 45.8% is influenced by other factors not examined in this study. These findings suggest that improving employees' job satisfaction should be prioritized to enhance productivity while maintaining a supportive organizational work culture.